Influence of synthesis parameters on g-C3N4 polysulfides trapping: A systematic study. (December 2021) - Versaci, Daniele; Cozzarin, Melina; Amici, Julia; Francia, Carlotta; Leiva, Ezequiel P.M.; Visintin, Arnaldo; Bodoardo, Silvia
Highligths: Systematic study of g-C3 N4 precursors and synthesis temperature for LiPSs trapping Double-layer implementation and optimization directly on sulphur cathode Syntheses carried out keeping in mind the feasibility of industrial scale-up Promising electrochemical performances for long-time cycling Performances correlated to the morphology and surface chemistry of g-C3 N4 Abstract: Beyond Li-ion batteries, one of the most promising technology is the Lithium-Sulphur (Li-S) not only for its higher theoretical energy density (about 2600 Wh kg −1 ) but because sulfur is relatively inexpensive and non-toxic. However, the Li-S battery suffers from "shuttle effect" of polysulfides. Thus, restricting shuttling means increasing cell performance and durability. DFT calculations showed that graphitic carbon nitride (g-C3 N4 ) exhibits strong interactions with Li2 S ( e.g. superior to graphene-like carbon) and acts as polysulfides trapping agent. In this work, the role of g-C3 N4, synthetized from different precursor and at different polycondensation temperatures was systematically studied, using a double layer approach for the electrode preparation, which ensures direct interaction between g-C3 N4 and soluble lithium-polysulfides. This systematic study confirms the importance of the morphological and superficial properties of the material. In particular, carbon nitride from urea precursor remarkably improves the performance of the sulphur cathode, increasing the specific capacity of the cell by 25% and improving its useful life over 500 cycles. According to the morphological characterization and the XPS analysis, benefits are achieved from polycondensation of urea at 550°C. The obtained g-C3 N4 shows the highest proportion of -NH2 species on the surface, which favours the interaction with polysulfides. Graphical abstract: Image, graphical abstract